Improvement of the interlayer bonding strength in a 3D-printed mortar with biocement sprayed into interlayer surfaces - Yifang Cao; Luming Shen; Abhijit Mukherjee; Ali Abbas; Daniel Dias-da-Costa (Virtual and Physical Prototyping)
This paper proposes a method to improve the interlayer bonding strength in 3D-printed mortars by spraying bacteria and cement solutions (biocement) into the interlayer surfaces. The effectiveness of this approach is assessed using splitting strength tests. SEM and X-ray mapping of calcium carbonate crystals formed on the interlayers is used to investigate the synergistic effect of biocement in the bonding. A competing mechanism between the increased water content from spraying the biocement solution (which reduces strength) and the biocementation (which increases strength) is identified. The interlayer bond strength is shown to increase up to nearly six times for a spray application of bacteria and cementation solution at printing intervals of 120 min. This advanced manufacturing approach has benefits and implications on the load-bearing strength of 3D-printed vertical structures.HighlightsThis paper proposes a bacteria spraying technique to improve 3D-printed mortar performance.Biocementation of sprayed bacteria and cementation solutions enhances interlayer strength.A competing mechanism between higher water content and biocementation is identified.Biocementation can potentially increase interlayer strength by nearly six times.Benefits and implications for 3D printed vertical infrastructure in digital construction sector.